Covalent Organic Framework Hosting Metalloporphyrin‐Based Carbon Dots for Visible‐Light‐Driven Selective CO2 Reduction. (9th July 2020) - Zhong, Hong; Sa, Rongjian; Lv, Haowei; Yang, Shuailong; Yuan, Daqiang; Wang, Xinchen; Wang, Ruihu
Abstract: The visible‐light‐driven photocatalytic CO2 reduction is one appealing approach to simultaneously mitigate the energy crisis and environmental issues. It is highly desirable but challenging to selectively and efficiently convert CO2 into desirable products. Herein, a covalent organic framework hosting metalloporphyrin‐based carbon dots (M‐PCD@TD‐COF, M = Ni, Co, and Fe) is first presented, which serves as heterogeneous catalysts for CO2 photoreduction. M‐PCD@TD‐COF not only enriches available COF‐based catalytic materials, but also provides suitable environment for CO2 adsorption and activation on metalloporphyrin‐based carbon dots. The advantages of the host environment in COFs are highlighted by the satisfactory catalytic activity and remarkable selectivity of CO2 ‐to‐CO conversion over H2 generation up to 98%. The photocatalytic system is effective for both pure CO2 and the simulated flue gas. This work provides new protocols for the rational design of COF‐based heterogeneous catalysts for selective CO2 photoreduction. Abstract : A covalent organic framework (COF) hosting metalloporphyrin‐based carbon dots is fabricated for CO2 photoreduction. The material provides a suitable environment for CO2 adsorption and the activation on carbon dots, resulting in efficient CO2 ‐to‐CO conversion with selectivity over H2 generation as high as 98%. This work provides new protocols for the construction of COF‐based heterogeneous catalysts for photocatalytic CO2 reduction.